Pengaruh Sales Promotion, Content Marketing Dan Shopping Lifestyle Terhadap Impulse Buying Pada Aplikasi Tiktok Shop (Studi Kasus Pada Mahasiswa Manajemen FEB UNISMA Angkatan 2020) - Mas, Hazim Achmad Ibnil; Wahono, Budi; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine and analyze the influence of sales promotion, content marketing and shopping lifestyle on impulse buying on the TikTok Shop application, either partially or simultaneously. The research method applied is a quantitative approach. The population used in this research is 474 Management Students of FEB UNISMA Class of 2020, however the students who use the TikTok Shop application are not known for sure. The sample results of this research were 80 students of Management Study Program FEB UNISMA class of 2020 with sample calculations using the Malhotra formula. The results of this research show that sales promotion, content marketing and shopping lifestyle simultaneously have a positive and significant effect on impulse buying on the TikTok Shop application. Meanwhile, partially, sales promotion, content marketing and shopping lifestyle have a positive and significant effect on impulse buying on the TikTok Shop application. Keywords: Sales Promotion, Content Marketing, Shopping Lifestyle, Impulse Buying, TikTok Shop App.